COMMUNITY EMPOWERMENT IN NATURAL RESOURCE MANAGEMENT BASED ON LOCAL WISDOM - Ramadani, Ipat (LPPM Universitas Bina Bangsa, 2025)
The aim of this research is to describe development in Indonesia which still ignores aspects of environmental sustainability. Development that is expected to provide benefits turns out to carry risks from its implementation. True development has a close relationship with the environment. When development cannot pay attention to aspects of environmental sustainability, the environment is not only deer but can also be destroyed. Environmental extinction means the extinction of humans themselves. Sustainable development is present as a paradigm that is expected to provide solutions to the negative impacts that arise as a result of development. In its implementation, the Indonesian Government has enacted Law Number 32 of 2009 concerning Environmental Protection and Management. Efforts that can be made to implement environmentally sound sustainable development in Indonesia include emphasizing environmental law, auditing and supervising AMDAL, RRAN and the community, as well as the need for a triangular partnership between the government, business world and civil society in an equal relationship without ignoring economic law. ecology, and civilization.